Maternal and Fetal Factors that Affect Preterm Birth at the Professor Ngoerah Central General Hospital - Budiani, Ni Nyoman; Sudarmi, Ni Luh; Ariyani, Ni Wayan (Jurnal Bidan Cerdas, 2024)
Introduction: Preterm birth occurs in 7-10% of all live births, leading to complications such as low birth weight, asphyxia, hypothermia, and hypoglycemia, which increase the risk of neonatal death. This research aims to prove the influence of maternal factors (age, occupation, marital status, gravida, hypertension) and conception results (number of fetuses and ruptured membranes) on preterm birth. Method: This correlational research, using a cross-sectional approach, was conducted at Prof. Ngoerah Hospital, Bali, in 2021. The study population included all women who gave birth in 2020, fully recorded in medical records, with a total sample size of 997 women, obtained through total sampling. Data were analyzed using crosstabulation, Chi-square test (X²), and binary logistic regression with computer assistance, setting significance at α 0.05. Results: Preterm birth was significantly influenced by maternal age (p=0.001), occupation (p=0.001), blood pressure (p=0.000), and the condition of the amniotic membranes (p=0.000). These factors collectively contributed to 22.7% of the variance in preterm births. Conclusion: Maternal factors such as age, occupation, blood pressure, and amniotic membrane condition significantly influence the incidence of preterm birth. Preventive measures, focusing on education before and during pregnancy, are crucial to reducing the risk of preterm births.